Evaluation of the Western blotting method for the diagnosis of congenital toxoplasmosis, - Jaqueline Dario Capobiango; Thaís Cabral Monica; Fernanda Pinto Ferreira; Regina Mitsuka-Breganó; Italmar Teodorico Navarro; João Luis Garcia; Edna Maria Vissoci Reiche
Abstract Objective: To evaluate the Western blotting method for the detection of IgG anti-Toxoplasma gondii (T. gondii) (IgG-WB) in the serum of children with suspected congenital toxoplasmosis. Methods: We accompanied 47 mothers with acquired toxoplasmosis in pregnancy and their children, between June of 2011 and June of 2014. The IgG-WB was done in house and the test was considered positive if the child had antibodies that recognized at least one band on IgG blots different from the mother's or with greater intensity than the corresponding maternal band, during the first three months of life. Results: 15 children (15.1%) met the criteria for congenital toxoplasmosis and 32 (32.3%) had the diagnosis excluded. The symptoms were observed in 12 (80.0%) children and the most frequent were cerebral calcification in 9 (60.0%), chorioretinitis in 8 (53.3%), and hydrocephalus in 4 (26.6%). IgM antibodies anti-T. gondii detected by chemiluminescence (CL) were found in 6 (40.0%) children and the polymerase chain reaction (PCR) for detection of T. gondii DNA was positive in 5 of 7 performed (71.4%). The sensitivity of IgG-WB was of 60.0% [95% confidence interval (CI) 32.3-83.7%] and specificity 43.7% (95% CI 26.7-62.3%). The sensitivity of IgG-WB increased to 76.0 and 89.1% when associated to the research of IgM anti-T. gondii or PCR, respectively. Conclusions: The IgG-WB showed greater sensitivity than the detection of IgM anti-T. gondii; therefore, it can be used for the diagnosis of congenital toxoplasmosis in association with other congenital infection markers.